Revolutionary no more : the disempowering effect of marriage on classic literary heroines. - Chia, Valerie Ying En. (2013)
Aside from their status as canonical works of English Literature and bestselling blockbusters of their time, another element uniting Samuel Richardson’s Pamela (1740), Jane Austen’s Pride and Prejudice (1813), and Charlotte Brontë’s Jane Eyre (1847), is their focus on courtship and marriage from a female perspective. In particular, these novels detail the struggles their protagonists face in their romance with men superior to them in class. Celebrated for their outspokenness and boldness in defying the patriarchal social script of their time which prescribed domesticity, passivity, and subservience as the standard for women, the three heroines (Pamela, Elizabeth, and Jane) notably reject the first proposal of some sort of formal arrangement (marriage/cohabitation) from their future husbands. Marriage is only consented to when their terms are met. Given the discrimination women were subjected to during the centuries in which these works were published, the heroines’ deviation from conventional social norms was both revolutionary and controversial to the readers of their day. This thesis contends, however, that contrary to popular interpretation and belief, not all three heroines are truly rewarded, as Pamela famously considers herself to be, by their radical class-crossing marriages. With the exception of Elizabeth, the other heroines suffer a loss of autonomy and agency soon after they become romantically involved with their prospective husbands. They are eventually reinscribed back into the patriarchal social script of their time and, with their revolutionary qualities subsumed, become neutralised as a threat to the status quo.